(untitled) (International Journal of Biomedical and Advance Research, 2015)
Objective: Cardio respiratory fitness in terms of maximum oxygen uptake [VO2max] reflects physical fitness of a person.VO2max is single best measure of cardio respiratory capacity and is considered as a bench mark to quantify cardiovascular function capacity and aerobic fitness. The main aim of study was to assess and compare the cardio respiratory fitness in terms of maximum aerobic capacity [VO2max] among the young adult male and female medical students of Maharishi Markandeshwar University [MMU], Mullana, Haryana. Method: A total of fifty seven young adult male [n=30] and female [n=27] students, around age group of 18-24 years were recruited by simple random sampling from Maharishi Markandeshwar University, Haryana.VO2max was estimated indirectly by following the protocol of Queens College Step Test [QCT] method. QCT is the simplest one to determine cardio respiratory fitness in terms of maximum oxygen uptake. Result: In present study it was found that mean value of VO2max for males was [45.66+8.96] ml/kg/min and for females it was [37.85+4.3] ml/kg/min. The mean value of VO2max was found significantly higher in male as compared to female students [P value 0.0001]. Conclusion: From the study it was concluded that our subjects fitted in the category of fair on cardio respiratory fitness scale, could be because of the decreased physical activity, unhealthy lifestyle behaviors as are established during the years of gaining education, which may influence adult behavior and health status. Physical fitness performance was better in male students than female students. Health promotion policies and physical activity programs should be designed to improve cardio respiratory fitness.